Synthesis, Spectral Studies and Antibacterial Activity of 3-(4-Phenyl-2,3-dihydro-1,5-benzodiazepin-2-yl)chromone - Prabha Sharma, Vinay; Kumar, Praveen (Asian Journal of Chemistry, 2014)
3-(4-Phenyl-2,3-dihydro-1,5-benzodiazepin-2-yl)chromone (PHBDC) has been synthesized by reacting 1-phenyl-3-(chromon-3-yl)-2-propene-1-one (chalcone) with o-phenylenediamine. Structures of chalcone as well as PHBDC were established on the basis of elemental analysis, IR and PMR spectral studies. 3-(4-Phenyl-2,3-dihydro-1,5-benzodiazepin-2-yl)chromone has been found to be antibacterial against bacillus bacteria some of which cause food poisoning, anthrax (a malignant boil), etc.